2014
DOI: 10.1007/s00296-014-2978-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-week combined exercise therapy on oxidative stress in female fibromyalgia patients

Abstract: The aims of this study were to investigate the effect of exercise therapy on the oxidative stress in fibromyalgia patients and relationship between oxidative stress and fibromyalgia symptoms. Thirty women diagnosed with fibromyalgia according to the American College of Rheumatology preliminary criteria, and 23 healthy women whose age- and weight-matched women were enrolled the study. Pain intensity with visual analog scale (VAS), the number of tender points, the fibromyalgia impact questionnaire (FIQ), the Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…In a study by Tetik et al, 21 plasma thiol levels were shown to be decreased in rheumatoid arthritis and primary osteoarthritis patients. Similarly, Altindag et al 32 and Sarifakioglu et al 34 found that plasma thiol levels were significantly lower in FMS patients compared with control subjects. However, due to the current measurement failure, they were only able to measure the thiol levels of homeostasis, while they were unable to measure disulphide and total thiol levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tetik et al, 21 plasma thiol levels were shown to be decreased in rheumatoid arthritis and primary osteoarthritis patients. Similarly, Altindag et al 32 and Sarifakioglu et al 34 found that plasma thiol levels were significantly lower in FMS patients compared with control subjects. However, due to the current measurement failure, they were only able to measure the thiol levels of homeostasis, while they were unable to measure disulphide and total thiol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study included an exercise-only group in their study design, which seemed to have no effects on levels of oxidative stress, in contrast to prior reports on exercise-only interventions [12,13,14,15]. Combined diet- and exercise-induced weight loss interventions may achieve an additional benefit with respect to oxidative stress, DNA repair, and telomere length.…”
Section: Discussionmentioning
confidence: 65%
“…Intensive physical exercise may adversely influence the balance between oxidative and anti-oxidative factors and, thus, cause increased levels of oxidative stress [11]. Nevertheless, several exercise-only interventions have reported a reduction of biomarkers of oxidative stress [12,13,14,15]. Thus, the evidence is not entirely consistent and suggests that there may be differences attributable to varying types of exercise interventions (e.g., duration, intensity, aerobic, anaerobic).…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, an increase in the activity of the enzyme glutathione reductase was observed after exercise (22). However, some studies have observed an increase in the catalase activity after exercise (23,24) some observed no change (25,26), and some found even lower (27) activity that could have implications on the role of the increase in glutathione as coenzyme glutathione oxidase. During the action of glutathione reductase, glutathione is regenerated and converted to oxidized glutathione that turns NADPH to glutathione again by glutathione reductase (2).…”
Section: Discussionmentioning
confidence: 96%